Crocin-I Protects Against High-Fat Diet-Induced Obesity via Modulation of Gut Microbiota and Intestinal Inflammation in Mice - Xiaoxian Xie; Mengya Zhang; Lei Sun; Ting Wang; Zhengyan Zhu; Ruonan Shu; Fengchun Wu; Fengchun Wu; Zezhi Li; Zezhi Li (Frontiers Media S.A., 2022)
Crocin-I can regulate physiological changes in the human body by altering inflammation and microbial composition. Gut microbiota are also involved in modulating the pathophysiology of obesity. However, crocin-I's effect on obesity and the mechanism underlying its effects on gut microbiota and inflammation remain poorly understood. Here, high-fat diet (HFD) -induced obese mice were administrated crocin-I (20 mg/kg/day) for 10 weeks using an oral gavage (HFD-C20 group). HFD-C20, HFD, and Normal chow (NC) groups were compared. The fat content, colon tissue inflammatory cytokine levels, gut microbiota, and short-chain fatty acids (SCFAs) levels were measured. We show that crocin-I reduced body weight and liver weight and improved glucose resistance in HFD-induced mice, and reduced the lipid accumulation in the liver. Strikingly, crocin-I alleviated intestinal microbial disorders and decreased the F/B ratio and the abundance of Proteobacteria in HFD-induced obese mice. Crocin-I also rescued the decrease in the levels of SCFAs and repaired altered intestinal barrier functioning and intestinal inflammation in HFD-induced obese mice. These findings indicate that crocin-I may inhibit obesity by modulating the composition of gut microbiota and intestinal inflammation.